PREVALENCE OF MULTIDRUG-RESISTANCE PATHOGENS ISOLATED FROM WOUND INFECTION PATIENTS VISITING COMBINED MILITARY HOSPITAL (CMH) PESHAWAR, PAKISTAN (The Research of Medical Science Review, 2024)
The main goal and aim of this study was to find out the prevalence of different bacterial pathogens and their antibiotic susceptibility in different patients having different sorts of wound infections. Total 200 positive pus samples were collected from patients of all genders and ages in the duration of three months. These samples were examined to detect the antibiotic susceptibility which has significant growth of pus producing pyogenic bacteria. The samples which were collected from patient’s wounds were then inoculated on Blood agar, MacConkey agar media and also Chocolate agar media for preliminary identification of pyogenic bacteria such as Pseudomonas spp, staphylococcus aureus, E. coli, Klebsiella specie, Enterococcus specie. After growth colonies were presumably identified according to colony formation, pigmentation, elevation and margins. After that the supposed isolates were then tested for further verification. The supposed isolates were then tested through biochemical tests for instance MIU Motility Indole Urea test, TSI Triple Sugar Iron test, Citrate utilization test, Coagulase test and Oxidase, the bacterial growth were then subjected to MHA media to detect the sensitivity/susceptibility of antibiotics using antibiotics discs. This study depicted that 64% men are more infected than women 36%. Among infectious agentsS.aureus (30%) was the most prevalent. E. coli 24% Pseudomonas24%, Klebsiellaspp.10%Streptococcus4%&Proteus spp 3%Acinetobacter spp. 3% and Enterococcus 2% were the least prevalent. And the minimum numbers of candida spp 0.83% were also detected. Mostly the Gram positive bacteria from our isolates were resistant against Cephalosporin group of antibiotics and were sensitive against Carbapenem group of antibiotics for instance Ceftazidime 94% and Cefixime 92% were extremely resistant through Staphylococcus aureus bacteria, against Enterococcus specie antibiotics Imipenem was 20% and Meropenem was 80% resistant. On the contrary the Gram-negative bacteria Pseudomonas specie Acinetobacter and E. coli depicted highly resistance towards the antibiotics. Prevalence of MDR to the antibiotics that were not resistant to pathogenic species decades ago was found to be emerging gradually to an alarming situation which is most likely due to the excessive usage, partial medication and self-medication along with the other factors.